Implikasi Metode Ummi dalam Meningkatkan Kualitas Membaca Al-Qur’an Anak Kelas A di TK IT Sahabat Qur’an Koba - Hikmah, Mutial (ICEJ : Islamic Childhood Education Journal, 2024)
This research describes the implications of the Ummi Method in Improving the Quality of Al-Qur'an Reading for Class A Children at the Friends of the Qur'an Koba IT Kindergarten. Based on the results of the researcher's observations, Class A of the Friends of the Qur'an Koba IT Kindergarten has implemented the ummi method in class A of the Friends of the Qur'an Koba IT Kindergarten. Where in class A, the children who are learning to read the Koran for the first time using the Ummi method are still not doing it well. There are several problems in implementing the Ummi method in class A of TK IT Friends of the Qur'an Koba, namely when they first learn to read the Al-Qur'an using the Ummi Method, the children are still confused because it is the first time learning. Children still don't know the rules of simple tajwid, the pronunciation of makhraj letters is not correct, reading with fashahah, and reading the Koran with an up and down rhythm. The purpose of this research is to find out how to apply the steps for reading the Al-Qur'an using the Ummi method in class A TK IT Sahabat Qur'an Koba using the Ummi Method and also the implications of the Ummi method in improving the quality of reading the Al-Qur'an using the Ummi Method in class A Kindergarten IT Friends of the Qur'an Koba.